Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.14198/raei.2017.30.10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the presence of Anglicisms in a Spanish internet forum: some terms from the fields of fashion, beauty and leisure

Abstract: The pervasive presence of English in Spain is unquestionable; indeed, a vast volume of literature has provided evidence of this fact. In this article, the remarkable presence of Anglicisms in a particular type of social media will be examined, namely the Spanish Internet forum enfemenino. The analysis covers three specific domains: beauty, fashion and leisure. The study focuses on a sample of English borrowings used in news articles published in this forum over the last 2 years (from January 2015 to March 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The penetration of anglicisms in various fields has been extensively examined by several authors in Spain. For example, the following fields have been explored: beauty and fashion (Luján-García 2017; Tejedor Martínez 2017); sports (Rodríguez González 2012; Rodríguez Medina 2016); TV commercials (García-Morales et al 2016); marketing (López Zurita 2018); toys and games (Luján-García 2015); even areas such as drugs (Rodríguez González 1994) and sex (Crespo-Fernández andLuján-García 2017, 2018). All these authors have reported that there is a remarkable number of anglicisms in Spanish, and that they are used with different functions.…”
Section: International Professional English and Anglicismsmentioning
confidence: 99%
“…The penetration of anglicisms in various fields has been extensively examined by several authors in Spain. For example, the following fields have been explored: beauty and fashion (Luján-García 2017; Tejedor Martínez 2017); sports (Rodríguez González 2012; Rodríguez Medina 2016); TV commercials (García-Morales et al 2016); marketing (López Zurita 2018); toys and games (Luján-García 2015); even areas such as drugs (Rodríguez González 1994) and sex (Crespo-Fernández andLuján-García 2017, 2018). All these authors have reported that there is a remarkable number of anglicisms in Spanish, and that they are used with different functions.…”
Section: International Professional English and Anglicismsmentioning
confidence: 99%